An Analysis of Indonesian Translation of Similes Used In Philip Pullman's Novel Entitled the Golden Compass - Farida Agoes; Muhammad Fajar Naufal; Nita Henita Koesoemah (Jurnal Bahasa Inggris Terapan, 2021)
This research has aimed to investigate the strategies used in translating similes found in “The Golden Compass”. The method applied in this study was descriptive-qualitative. The data for this study were collected from The Golden Compass written by Philip Pullman and its Indonesian version translated by B. Sendra Tanuwidjaja. The collected data were analyzed based on Larson's theory dealing with similes and Pierini's theory dealing with translation strategies to translate the similes. The results show that the strategy of literal translation (the same image retention) dominates the highest rank with 73 similes (84.9%), followed by replacement of the image with a different one with 4 similes (4.7%), the same image’s retention plus explicitness of similarity feature(s) with 4 similes (4.7%), the image’s replacement with a gloss with 3 similes (3.5%), omission of the simile with 2 similes (2.3%). The dominant use of the literal translation (retention of the same image) implies that the translator thought that most images in the similes are familiar in the target language and are not necessary to change.